TINJAUAN YURIDIS TERHADAP PENGINGKARAN PERJANJIAN KERJASAMA (STUDI KASUS PADA WORLD TRAVEL MARKETING CO., LTD. KOREA KEPADA PT. CAMPUHAN AGUNG) - I Made Dwitya Surya Nugraha; Komang Febrinayanti Dantes; Ni Ketut Sari Adnyani (Universitas Pendidikan Ganesha, 2023)
Cooperation agreement in dealing with Korean tourists in Bali made between World Travel Marketing, Co., Ltd. Korea with PT. Campuhan Agung as the basis of the legal relationship about the agreement that have been agreed, which give rise to rights and obligations for the parties. This study aims to review and analyze about: 1). defaults committed by foreign companies domiciled abroad against domestic companies, 2). legal force of the letter of cooperation agreement that has been noted (waarmerking) and recorded by a Notary, 3). legal consequences for the existence of default, 4). solution method of defaults. Furthermore, all information obtained from the source persons are studied and analyzed qualitatively. The research results show that there are elements that caused to be default, such as: an element of intentionality and / or element of negligence committed by Mr. Lee Kun Rok as Chairman of World Travel Marketing, Co., Ltd. Korea to be able getting much profits unilaterally and he did not want to pay agent fees to PT. Campuhan Agung in accordance with the content of the agreement letter that has been agreed. Agent fee is a right that must be accepted by PT. Campuhan Agung as compensation for providing to be able running tourism business protection to World Travel Marketing, Co., Ltd. Korea in Bali.